An unusual clinical manifestation of a relapsed typical pulmonary carcinoϊd tumor. (2021) - Belloumi, Nidhal; Hamdi, Mariem; Braham, Emna; Bachouch, Imène; Chermiti Ben Abdallah, Fatma; Mezni, Faouzi; Fenniche, Soraya
Abstract: Typical carcinoid tumors of the lungs carry an excellent prognosis after complete surgical excision. However, recurrence of these cancers remains poorly described in the literature and may occur many years after surgery. We report a case of carcinoid tumor of the lung. Clinical presentation and follow-up were uneventful. The 55 years old patient had got a surgical removal of a huge typical carcinoid tumor of the left lung. A left pneumonectomy with a mediastinal lymph node resection were performed. Thirteen years later, paraneoplastic acromegaly revealed a pulmonary and extrapulmonary recurrence of the tumor. We prescribed a chemotherapy regimen including Cisplatin and Etoposide. Endocrine paraneoplastic syndromes are related to mutations in specifically known genes. Several mutations may become a promising therapeutic target in the future. In the case of neuro-endocrine pulmonary tumors, authors described BCOR gene mutation as an oncogenic development inducer and an eventual generator of ectopic tumoral secretions. The more we get familiar with carcinoid tumor mutations, the closer we get to targeted therapy for non-resectable tumors.